(untitled) (Innovative professional education, 2025)
The use of innovative teaching methods in literature lesson ensures the formation of the spiritual word of students. The use of nonstandard classes helps to fulfill the most important function – to educate a person with the miraculous power of words. Career oriented lesson promote love for the chosen profession